MCSE designing security for a Windows Server 2003 network exam 70-298 - Khnaser, Elias N.; Hunter, Laura E. (Rockland, MA : Syngress, 2004)
"MCSE Exam 70-297 Study Guide & DVD Training System: Managing and Maintaining a Windows Server 2003 Environment for an MCSA Certified on Windows 2000 is a one-of-a-kind integration of text, DVD-quality instructor led training, and Web-based exam simulation and remediation. This system gives you 100% coverage of the official Microsoft 70-297 exam objectives plus test preparation software for the edge you need to pass the exam on your first try."
Cover; Objective Map; Contents; Foreword; Designing a Secure Network Framework; Securing Servers Based on Function; Designing a Secure Public Key Infrastructure; Securing the Network Management Process; Securing Network Services and Protocols; Securing Internet Information Services; Securing VPN and Extranet Communications; Securing Active Directory; Securing Network Resources; Securing Network Clients; Self Test Questions, Answers, and Explanations; Index
"Study guide & DVD training system"--Cover.
Includes index.
Keywords: Electronic data processing personnel -- Certification; Microsoft software -- Examinations -- Study guides; Microsoft Windows server; Electronic books; Study guides